Effect of art therapy in anxiety and depression, training sociocultural and reducing prison recidivism in inmate - Pilar Mª Domínguez Toscano; Mª Dolores López Martínez (Arteterapia)
This document provides an overview of art therapy programs implemented in prisons in the world, assessing its effects in rehabilitation programs for prison population. Report also offers art therapy program developed during the years 2006 to 2009, in the prison Huelva II. Objectives, methodology and results of the quantitative and qualitative assessment of their influence on levels of anxiety and depression are presented, and the effect obtained in prison recidivism and the sociocultural training.